Stained glass windows - Ghosh, Ayan (Jio Institute, 2023)
Frederick W. Stevens was primarily influenced by Gothic architecture, and it is in Gothic that most of his projects were executed. Within the Gothic genre, Stevens had a particular liking for Venetian Gothic, which originated in Italy in the twelfth century. Inspired from Venetian Gothic, Stevens used stained-glass windows extensively throughout the BMC building.